Tinjauan Sistematis terhadap Efektivitas Model Project Based Learning (PjBL) untuk Mendukung Kemampuan Pemecahan Masalah: Penelitian - Jesica Triani Purba; Corry Yulia Fitri; Dinda Permata Sari; Faidhol Anwar; Dinda Chairunnisa Jalih; Uvi Karmila; Ziyad Muhammad Sulthon El Barqy; Fitri Damayanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study systematically reviews the effectiveness of Project-Based Learning (PjBL) and its variants, including POPBL and PjBL-STEM, in improving problem-solving skills, higher-order thinking skills, and learning outcomes in Mathematics and Science. Drawing on ten journal articles encompassing Systematic Literature Reviews, meta-analyses, and empirical studies such as quasi-experiments and classroom action research, the findings consistently show that PjBL is more effective than conventional methods, particularly for complex subject matter. Meta-analytic evidence also indicates a large effect size in fostering scientific creativity. Beyond cognitive gains, PjBL supports the development of positive student character. However, its implementation within the Merdeka Curriculum still faces challenges, particularly teacher administrative burdens, limited time allocation, and students’ readiness for collaborative work.